2005
DOI: 10.1007/s10750-005-1696-x
|View full text |Cite
|
Sign up to set email alerts
|

Diatoms from two macro-tidal mudflats in Chignecto Bay, Upper Bay of Fundy, New Brunswick, Canada

Abstract: Mudflat research is dispersed among several fields (ecology, sedimentology), each with its own focus and methodology. Consequently, although the volume of mudflat literature is considerable, our understanding of mudflat ecology remains fragmented. For example, little is known about the structure of microbial communities outside Western Europe. Here we present the first North American specific composition and densities of live mudflat diatoms and relate them to properties of their environment on two closely loc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 61 publications
0
15
0
Order By: Relevance
“…This is a surprising result, as diatoms are known to be an important source of FAs (Huggins et al 2004), particularly some longer chain PUFAs (Ackman et al 1964;Dunstan et al 1993), and diatoms make up the majority of microphytobenthos on mudflats in the Bay of Fundy (Trites et al 2005). Concentration and quality of FAs in diatoms varies with season, ultraviolet radiation, light, and species (Dunstan et al 1993;Huggins et al 2004;Guihéneuf et al 2010;Chen 2012), so it is possible that the conditions present on our mudflats are not conducive to high FA concentrations.…”
Section: Fig 2 (A)mentioning
confidence: 95%
See 1 more Smart Citation
“…This is a surprising result, as diatoms are known to be an important source of FAs (Huggins et al 2004), particularly some longer chain PUFAs (Ackman et al 1964;Dunstan et al 1993), and diatoms make up the majority of microphytobenthos on mudflats in the Bay of Fundy (Trites et al 2005). Concentration and quality of FAs in diatoms varies with season, ultraviolet radiation, light, and species (Dunstan et al 1993;Huggins et al 2004;Guihéneuf et al 2010;Chen 2012), so it is possible that the conditions present on our mudflats are not conducive to high FA concentrations.…”
Section: Fig 2 (A)mentioning
confidence: 95%
“…This is not surprising and has also been documented in other areas of their range (e.g., Skagen and Oman 1996). In the Bay of Fundy, both polychaete worms and biofilm (consisting primarily of diatoms and the extracellular polymeric substances that they produce; Trites et al 2005) now appear to contribute substantially to the diet (Quinn and Hamilton 2012), and other prey such as ostracods can be important if present in sufficient quantities (MacDonald et al 2012). The inclusion of biofilm is consistent with recent studies of related shorebird species (Kuwae et al 2008(Kuwae et al , 2012Jardine et al 2015), in which it has been found to be an important dietary component.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, tidal state (incoming or outgoing) was coded as a pair of nominal response variables (TIDEIN and TIDEOUT, respectively). Statistical analysis was similar to that described in Kaczmarska et al (2000) and Trites et al (2005), but with options more appropriate for this data set. CCA was performed on log transformed [ln(Ay + B); A = 1, B = 1] calculated species cell densities from each sample.…”
Section: Statistical Analyses and Terminologymentioning
confidence: 99%
“…It is well known that physical properties of sediments play a fundamental role in the nature of the microphytobenthos assemblage that colonizes sediments (Trites et al 2005). The settlement of large benthic diatom biomasses is prevented in sandier, unstable sediments, where the development of colonies on the open surface of sand grains is inhibited by agitation (McIntire and Ampsoker 1986).…”
Section: Discussionmentioning
confidence: 99%